Edible nanocoating: The properties of different casting methods and different types of nanoparticles incorporated with polysaccharides-based materials / Nur Haznina Haron, Noor Asnida Asli, and Nadya Hajar - Haron, Nur Haznina; Asli, Noor Asnida; Hajar, Nadya (2021)
Good quality foods, such as fresh fruits can be preserved by using nanotechnology which will prolong the shelf-life of the foods. Nowadays, environmental pollution and increment of food waste issues are concerned by the world community. Consequently, several studies have focused on developing and applying nanocoating technology based on edible and biodegradable materials. This review discusses the properties of solvent and extrusion of casting methods and the properties of different types of metal nanoparticles incorporated in polysaccharides, a biopolymers material. Casting is defined as a process of pouring a liquid material, such as plastics or metals into a mould and allowing it to dry and hard. The different casting methods will affect the bubble formation, water vapour permeability, and tensile strength properties of the coatings or films. Metal nanoparticles such as zinc oxide, silver, and titanium dioxide nanoparticles have become an interesting component of a biodegradable biopolymer coating involving polysaccharide-based materials. Polysaccharides-based materials such as chitosan, pullulan and cellulose based- materials are used to form edible coatings or films that have excellent film-forming properties. The incorporation of nanoparticles into polysaccharides-based coating or film leads to the development of nanocoating or films with improved antibacterial, antifungal, mechanical, and water-resistant properties. The nanocomposite polysaccharide incorporated with zinc oxide nanoparticles is the most effective in enhancing the antibacterial, antifungal, mechanical and water-resistant properties of the coatings or films which maintain the quality, extend the shelf-life and decrease food waste.